2015
DOI: 10.1097/md.0000000000002132
|View full text |Cite
|
Sign up to set email alerts
|

Increased Risk of Intracerebral Hemorrhage Among Patients With Hepatitis C Virus Infection

Abstract: This research explored whether hepatitis C virus (HCV) infection leads to the development of intracerebral hemorrhage (ICH).Using Taiwan National Health Insurance claims data, 9023 patients newly diagnosed with HCV infection between 2000 and 2010 were identified, and 36,092 age- and sex-frequency-matched patients without HCV infection were selected randomly as the control group. The risk of ICH for patients with HCV infection and comorbidities of diabetes, hypertension, ischemic heart disease, hyperlipidemia, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
4

Year Published

2016
2016
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 30 publications
0
16
0
4
Order By: Relevance
“…Worryingly, some studies also suggested a significant association between HCV and cerebral hemorrhages[192,193], and a recent large Taiwanese cohort study extended the association between HCV and atherosclerosis by showing that HCV-infected patients had an increased risk of peripheral artery disease compared to non-HCV control subjects[194]. …”
Section: Hcv Infectionmentioning
confidence: 99%
“…Worryingly, some studies also suggested a significant association between HCV and cerebral hemorrhages[192,193], and a recent large Taiwanese cohort study extended the association between HCV and atherosclerosis by showing that HCV-infected patients had an increased risk of peripheral artery disease compared to non-HCV control subjects[194]. …”
Section: Hcv Infectionmentioning
confidence: 99%
“…Two cases of intracranial hemorrhage were found only in first group’s patients. Intracranial hemorrhage was also reported before in untreated hepatitis C patients[ 35 , 36 ], but no evidence of ICH with pegIFN plus RBV was seen previously. In our findings ICH may also be due to HCV not because of SOF that needs further studies on a large scale.…”
Section: Discussionmentioning
confidence: 65%
“…However, their study lacked renal function data before IBT and background matching between cohorts. Despite conventional factors like age, being male, smoking, hypertension, diabetes, and drinking alcohol [ 23 ], HCV contributed to hemorrhagic stroke [ 24 , 25 ], liver cirrhosis [ 26 28 ], and unstable hemostasis [ 29 ]. Moreover, HCV was critically involved in systemic atherosclerosis, vascular remodeling, ectasia change, and microaneurysms, which manifested as cerebral microbleeds (CMBs) in the MRIs of patients with advanced hepatic fibrosis [ 30 ].…”
Section: Discussionmentioning
confidence: 99%